KEBIJAKAN SINGLE PRESENCE POLICY TERHADAP STRUKTUR KEPEMILIKAN BANK PASCA KONSOLIDASI BANK UMUM - Marwah Hasna Lathifah, (Jurnal USM Law Review, 2022)
The purpose of this research is to analyze the changes in the banking ownership structure policy related to the single presence policy after the issuance of OJK Regulation No.12/POJK.03/2020 concerning Commercial Bank Consolidation, and to examine the impact of single presence policy on the implementation of OJK Regulation Consolidated Bank. The single presence policy was established with the aim of increasing banking resilience, especially for the banks that are distressed and need to be rescued. However, this policy is considered irrelevant to current conditions and hinders efforts to rescue the distressed banks. Therefore it's important to issue the OJK Regulation on the Consolidation of Commercial Banks in order to provide relaxation on banking ownership policy for parties who want to take the corporate actions. This study uses a qualitative research method with a normative juridical approach. The novelty in this research refers to OJK Regulation No.12/POJK.03/2020 concerning The Commercial Bank Consolidation regarding the adjustment of bank ownership structure, which overrides the single presence policy in the previous regulations. Based on the research of this study, after the OJK Regulation many local and foreign investors who want to acquire national banks to be transformed into digital banks. In this regard, OJK needs to be more careful in terms of foreign ownership in national banks in order to prevent negative implications for the long-term national economy.